Prevalensi kejadian nyeri leher pada siswa SD Negeri 3 Mas, Desa Mas, Kecamatan Ubud yang menggunakan tas punggung - Ni Made Hita Husmarika; Muliani muliani; Yuliana yuliana (Department of Anatomy, Medical Faculty, Universitas Udayana, Bali-Indonesia, 2019)
Background: The incidence of neck pain abroad and in Indonesia is relatively high. The incidence of neck pain is caused by physical influence, one of them is the use of a backpack which is especially experienced by elementary school students. Aim: This study aimed to determine the prevalence of neck pain in students of SD Negeri 3 Mas, Mas, Ubud who using backpacks. Method: This study was descriptive cross-sectional study. The sampling technique use total sampling. The subjects were 79 students of SD Negeri 3 Mas, Mas, Ubud who met the inclusion and exclusion criteria. Inclusion criteria included students were willing and using backpacks while the exclusion criteria were students with infectious diseases or traumatic bone or muscle. Research data are primary data obtained from questionnaires and direct measurements by researchers. Results: Prevalence of neck pain in students of SD Negeri 3 Mas, Mas, Ubud using backpacks was 45.6%. The proportion of neck pain is more frequent in students with bag weight <10% body weight (47.0%), students who use backpacks >30 minutes (high duration) with any transportation (100%), non-obese students (46.6%) and female students (50.0%).